Gravity and the behavior of unicellular organisms - Häder, Donat-Peter (Developmental and cell biology series, 2005)
How do single cells know where is up and down? What is their ecological benefit? How can they be used to study the mechanisms of gravity perception? Historical and current approaches are summarised in order to answer these basic questions of interest to biologists as well as space and gravitational scientists.